Secure e-government web services - Mitrakas, Andreas; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Ave., Hershey, PA, 17033, USA), 2007)
"This book addresses various aspects of building secure E-Government architectures and services; it presents views of experts from academia, policy and the industry to conclude that secure E-Government web services can be deployed in an application-centric, interoperable way. It addresses the narrow yet promising area of web services and sheds new light on this innovative area of applications"--Provided by publisher.
1. Towards secure e-government / Andreas Mitrakas ... [et al.] -- 2. Building innovative, secure, and interoperable e-government services / A. Kaliontzoglou, T. Karantjias, D. Polemi -- 3. Trust models for ubiquitous mobile systems / Mike Burmester -- 4. Trust and security in ambient intelligence / Andrea Servida -- 5. Biometric authentication in broadland networks for location-based services / Stelios Thompoulos, Nikolaos Argyreas -- 6. Secure online metering for a liberalized energy market / Christoph Ruland -- 7. Deployment of e-government municipal services / Nikolaos Oikonomidis, Sergiu Tcaciuc, Christoph Ruland -- 8. E-government and denial of service attacks / Aikaterini Mitrokotsa, Christos Douligeris -- 9. Certificate management interoperability for e-government applications / Andreas Mitrakas -- 10. Privacy- enhanced identity management for e-services / Claudio Ardagna ... [et al.] -- 11. A protocol for anonymous and accurate e-polling / Danilo Bruschi, Andrea Lanzi, Igor Fovino -- 12. Secure multiparty/multicandidate electronic elections / Tassos Dimitriou, Dimitris Foteinakis -- 13. Requirements on cross-agency processes in e-government / Jeffrey Gortmaker, Marijn Janssen, Rene Wagenaar -- 14. Model driven security for inter-organizational workflows in e-governent / Michael Hafner ... [et al.] -- 15. A formalized design method for building e-government architectures / Alexandros Kaliontzoglou ... [et al.] -- 16. Towards building e-government on the grid / Ying Li, Yu Chen, Minglu Li -- 17. Service-oriented architecture for seamless and interoperable service delivery / Elena Mugellini, Omar Khaled, Maria Pettenat.
Includes bibliographical references and index.
Also available in print.
Mode of access: World Wide Web.
Title from PDF t.p. (viewed on July 14, 2010).
Keywords: Electronic government information -- Security measures -- United States; Internet in public administration -- United States; Electronic government information -- United States; Electronic books